Effects of Work Stress and Role Conflict on Employee Discipline in the Operational Division of Lippo Mall Karawaci Tangerang - Dika Vivi Widyanti; Suharmanto - Suharmanto; Bagas Putra Pradana (Admisi dan Bisnis, 2023)
A company has human resources, where employee performance is one measure of the company's success, while work stress and work discipline are both things that can affect performance. This study aims to determine the effect of work stress and role conflict on employee discipline. The population used is the employees of the operational division of Lippo Mall Karawaci Tangerang. The data analysis method used is path analysis. Path analysis method is used to analyze the relationship pattern between variables